Konstruksi Identitas Homoseksual Melalui Performativitas dalam Novel Permen Gan? Karya Dae Mahanta: Kajian Teori Queer Judith Butler - Tegar Prasetyo (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study examines the construction of homosexual identity in Dae Mahanta’s novel Permen Gan?, employing Judith Butler’s queer theory framework with a focus on performative concepts. The contemporary novel was selected for its representation of the popularity of homosexual narratives among Indonesia’s younger generation and its textual framework for character identity formation. The research aims to describe three forms of performative behavior: (1) character appearance and physicality, (2) character discourse, and (3) character sexual activity. A qualitative approach based on text analysis was employed, utilizing literature review and citation documentation for data collection. Data analysis identified citation mechanisms, subversion, and parody within performative practices. The findings reveal that homosexual identity is not portrayed as an innate biological essence but rather as the result of fluid and unstable performative repetition. The performative nature of performances demonstrates that expressions of masculinity or femininity do not automatically determine sexual orientation. The performative aspects of discourse serve as both a medium for identity affirmation and negotiation with heteronormative norms. Sexual performance reflects desires constructed through imagination and same-sex interactions. These findings confirm that novels not only mirror social realities but actively intervene in gender and sexuality frameworks in Indonesia. This study contributes to advancing queer studies in contemporary Indonesian literature while deepening understanding of sexual identity construction dynamics in fiction.